(untitled) (Atti del Sodalizio Glottologico Milanese, 2021)
Modern Mediterranean is a multicultural and multilingual environment where written communication shows a high variability. The present work aims at shedding light on a specific set of Greek documents dating from the 15th and 16th century and belonging to the collection Miscellanea Documenti Turchi of the Venetian State Archive. It proposes that, by analysing the lexical variability, the textual patterns and the pragma-linguistic features of such documents, their production can be explained within the framework of a text community which develops within a community of practice.